Silica-rich Sodalite Synthesis: The Effect of Variations in Ultrasound Treatment and Hydrothermal Temperature - Sriatun Sriatun; Marta Chandra Anikke Putri; Hanifa Zakiyatul Urbach; Adi Darmawan; Widayat Widayat; Heru Susanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Silica-rich sodalite zeolite has been synthesized by ultrasound treatment and hydrothermal temperature variation. This study aimed to determine the effect of ultrasound treatment and hydrothermal temperature variations on the crystallinity, hydrophobicity, and structural properties of silica-rich sodalite zeolite. The synthesis was conducted by reacting a sodium aluminate and sodium silicate solution by varying Si/Al ratios of 20, 30, 40, 60, 80, and 90. The next step was to characterize the product. The product with the best crystallinity was used as a reference to determine the effect of ultrasound and hydrothermal temperature. The reaction gel was treated with and without ultrasound and hydrothermal using autoclave at 100, 150, and 200°C for 24 hours. The last step was the product characterization using XRD, FTIR, and GSA. The XRD showed similarity peaks at 2θ = 14.058°; 24.41°; 31.73°; 34.75°; 42.88°. The best crystallinity was silica-rich sodalite zeolite with a Si/Al ratio of 30. Meanwhile, silica-rich sodalite zeolite peaks were obtained at 2θ = 14.16°, 24.66°, 31.99°, 35.13°, and 43.39° by ultrasound treatment and hydrothermal temperature variation (100, 150, and 200°C). Ultrasound treatment revealed the presence of other peaks besides sodalite at 2θ = 19.05° and 27°, where these peaks were referred to as SAPO-56. In conclusion, the degree of crystallinity increased with increasing temperature, decreasing Si-OH/Si-O-Si showed increased hydrophobic properties. Increasing the hydrothermal temperature of 150 and 200°C with and without ultrasound treatment increased the surface area significantly to 114.137 m2/g and 160.717 m2/g, and the pore volume of sodalite with a Si/Al ratio of 30 to 0.318 cc/g and 0.274 cc/g.